2017
DOI: 10.1080/09712119.2017.1324456
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sea buckthorn (Hippophae rhamnoides L.) fruit residues on performance and egg quality of laying hens

Abstract: The experiment was conducted on Isa Brown laying hens to study the effects of sea buckthorn fruit residues on hen performance and quality of eggs. The total number of 1440 eighteen-week-old pullets Isa Brown was divided into two groups (720 each) including 24 subgroups (30 hens). The experimental group was fed diets in which 5% of the wheat was replaced by sea buckthorn fruit residues. The control group was fed diets without any colour additives. Egg production and intensity of laying hens were evaluated in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Results of the CIELab analysis showed that feeding laying hens with a diet supplemented with 2% dried sea buckthorn pomace during 4 weeks determined a significant increase of yolk redness (a* values, from −1.32 to 4.41), yellowness (b* values, from 39.09 to 49.21) and Chroma (from 40.40 to 49.41) as compared with the control group, while L* values were not significantly affected. Similar trends have been reported by several previous studies [32,42]. After 3 weeks of feeding, yolks from the group supplemented with dried sea buckthorn pomace showed a significantly higher content of total carotenoids deposition (17.613 mg/kg) as compared with those from the control group (15.385 mg/kg).…”
Section: Yolk Color and Carotenoid Concentration In Eggs Yolksupporting
confidence: 90%
See 3 more Smart Citations
“…Results of the CIELab analysis showed that feeding laying hens with a diet supplemented with 2% dried sea buckthorn pomace during 4 weeks determined a significant increase of yolk redness (a* values, from −1.32 to 4.41), yellowness (b* values, from 39.09 to 49.21) and Chroma (from 40.40 to 49.41) as compared with the control group, while L* values were not significantly affected. Similar trends have been reported by several previous studies [32,42]. After 3 weeks of feeding, yolks from the group supplemented with dried sea buckthorn pomace showed a significantly higher content of total carotenoids deposition (17.613 mg/kg) as compared with those from the control group (15.385 mg/kg).…”
Section: Yolk Color and Carotenoid Concentration In Eggs Yolksupporting
confidence: 90%
“…Contrarily, Abou-Elkhair et al [52] showed that the dietary inclusion of 5 g/kg red pepper improved (p < 0.05) egg production, feed conversion ratio compared with control. By replacing 5% of the feed wheat with sea buckthorn fruit residues (berries resulting after extracting the juice and then dried), Shaker et al [32] did not record any difference in the hen's performance.…”
Section: Performance Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…In broiler chickens, dietary supplementation of sea buckthorn flavones has been demonstrated to affect growth performance and fat deposition by regulating lipid metabolism [6]. Interestingly, supplementation of SBP to laying hens showed beneficial effects on the total number of laid eggs and the egg yolk color [7].…”
Section: Introductionmentioning
confidence: 99%